MORPHOLOGICAL, BIOCHEMICAL, AND AGRONOMIC TRAITS OF SELECTED Origanum majorana L. CLONES - Muneera Lateef; Mehmet Emin Çaliskan (Journal of Animal and Plant Sciences, 2026)
Origanum majorana L. is known for its essential oil yield (EOY) and herbs usage worldwide which contain several secondary metabolites and possess pharmaceutical, medicinal, and culinary properties. There have been a lot of developments in plant production, i.e., from generating new varieties to analyze their properties to explore new and innovative, sustainable methods for their cultivation but Origanum majorana L. species got less attention. In this study, Origanum majorana L. clones were selected on the basis of morphology and biochemical traits. Fifty clones were selected from 450 Turkish local Origanum majorana L. clones on the basis of high growth rate, lush green color and better adaptability in the studied region. Growth parameters were recorded at different phenological stages, while dried shoot samples of Origanum majorana L. were used to determine essential oil yield, antioxidant activity and secondary metabolites constituents. The results of the current study showed that among 50 selected clones, 52% of clones were shown to have an erect growth habit with high performance rate as compared to bushy clones that were in average of 48%. The clone ORM 025 showed high biomass and ORM 016 higher EOY (2 ml 100-1 g) while ORM 014 showed high antioxidant activity. The high number of secondary compounds were observed from ORM 006 and ORM 044 (50 compounds) while ORM 014 clone produced the lowest (18 constituents only) number of secondary metabolite constituents proving an inverse relationship between EOY and secondary metabolite constituents. Overall, ORM 025, ORM 016 clones proved high biomass and EOY, ORM 014 showed high antioxidant activity and ORM006 and ORM 044 produced a high number of compounds proving the efficiency of these genotypes for further breeding programs. The present study focuses on finding the elite clone among fifty which should have properties like high EOY and herbage yield. In future, molecular studies and in vitro studies are needed to check the genetic diversity and reproducibility of these fifty clones.
Keywords: sweet marjoram; clones; morphology; antioxidants; essential oil